The Importance of Contraceptive Use in Spacing Pregnancies and Building a Healthy and Prosperous Family - Iga Retia mufti; Intan Karlina; Mila Latifah Farida; Aprilia Najwa Ananta; Lunetta Syahla Salsabila; Melanie Julianti; Milka Shaliha Nugroho; Nadia Herliana; Nabila Musafa’ah Nurrahmi; Resa Rosmayanti; Santi Nurmala; Sifanni Tri Rahmania; Sheira Shiva Puspita (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The use of contraception aims to regulate the number of children and the spacing of births to improve family welfare and control population growth. However, many people in Indonesia still harbor fears about using contraception. This study aims to determine the effect of knowledge levels among couples of reproductive age on contraceptive use. The research was conducted at Posyandu Graha Berseri, located in Komplek GBR 3 Rt. 07/Rw 25, Cilame Village, Ngamprah District, Bandung Barat Regency. A qualitative approach with a cross-sectional method was employed to assess the knowledge levels and contraceptive types used by Women of Reproductive Age (WRA). The sample consisted of 35 respondents selected through cluster random sampling. The results showed that the knowledge level of couples of reproductive age regarding contraceptive use was significantly low. The cross-sectional analysis revealed that 91% of respondents were categorized as "Very Good," while none fell into the "Poor" category. Overall, the knowledge level among couples of reproductive age was deemed good. This activity successfully expanded the awareness of Women of Reproductive Age regarding the definition, side effects, benefits, and appropriate timing for contraception use.